2019
DOI: 10.1002/jcp.28701
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Melatonin attenuates TNF‐α‐mediated hepatocytes damage via inhibiting mitochondrial stress and activating the Akt‐Sirt3 signaling pathway

Abstract: The role of mitochondrial dysfunction and its molecular mechanism in inflammationinduced acute liver failure (ALF) remain unknown. Despite the numerous studies performed to date, very few therapies are available for inflammation-induced ALF.Therefore, our study is aimed to explore the regulatory effects of mitochondrial stress and the Akt-Sirt3 pathway on the development of TNF-α-induced hepatocyte death and assess the therapeutic effects of melatonin on the damaged liver. Our results exhibited that TNF-α trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Melatonin targets mitochondria and functions as an apex antioxidant ( 45 ), and besides being taken up by cells from the circulation, melatonin might be produced in mitochondria ( 45 ). Melatonin can attenuate TNF-α-mediated hepatocyte damage through SIRT3-mediated mitochondrial-stress inhibition ( 18 ), and counteracts mitochondrial dysfunction in the skeletal muscle of septic mice ( 46 ). Furthermore, SIRT3-mediated mitophagy protects tumor cells against apoptosis under hypoxia ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin targets mitochondria and functions as an apex antioxidant ( 45 ), and besides being taken up by cells from the circulation, melatonin might be produced in mitochondria ( 45 ). Melatonin can attenuate TNF-α-mediated hepatocyte damage through SIRT3-mediated mitochondrial-stress inhibition ( 18 ), and counteracts mitochondrial dysfunction in the skeletal muscle of septic mice ( 46 ). Furthermore, SIRT3-mediated mitophagy protects tumor cells against apoptosis under hypoxia ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that melatonin treatment elevates the expression and activity of SIRT1 in various animal/cell sepsis models, and alleviates sepsis-induced brain and liver injury, as well as cardiac dysfunction (10,(13)(14)(15)(16). Moreover, melatonin can activate SIRT3 to reduce oxidative stress (17) and inflammation (18), induce autophagy (18), and preserve mitochondrial function (19,20). Its effect on sepsis is also reportedly related to the regulation of other SIRTs, including SIRT2 (21,22), SIRT4 (23), and SIRT6 (24).…”
Section: Introductionmentioning
confidence: 99%
“…LPS or TNF-α alone cause a lower specific damage to hepatocytes (21). Previous studies have shown that D-GalN can be used as a sensitizer in LPS-induced liver injury; specifically, uridine triphosphate is depleted by the galactose pathway, which inhibits protein synthesis, resulting in ROS-mediated liver damage (2224). Therefore, LPS can be used in combination with D-GalN to induce ALF in animal models (25,26) and TNF-α combined with D-GalN can be used to create an L02 cell injury model (27); these models have been widely used to explore and develop new liver protection agents for the treatment of ALF.…”
Section: Discussionmentioning
confidence: 99%
“…It can damage the integrity, increase the permeability of the intestinal barrier, and promote the secrete of proinflammatory cytokine to amplify the inflammatory response ( Nguyen et al., 2018 ). TNF-α combines with TNF receptor 1, which is a membrane receptor, and leads to apoptosis by activating the TNF receptor 2 associated death domain protein, Fas-associated death domain protein (FADD), FADD like IL-1β converting enzyme, caspase-3, and caspase-9 ( Song et al., 2019 ). Furthermore, intestinal flora can convert tryptophan to indole-3-formaldehyde which can alleviate the mouse dermatitis through suppressing the cytokine secretion of Th2 cells ( Gostner et al, 2016 ).…”
Section: Gut Microbiome and Inflammationmentioning
confidence: 99%